The Hidden Cost of Organ Sale - Rothman, S. M.; Rothman, D. J. (American journal of transplantation, 2006)
The idea of establishing a market for organs is now the subject of unusual controversy. Proponents emphasize the concept of autonomy; opponents invoke fairness and justice. The controversy, however, has given sparse attention to what it would mean to society and medicine to establish a market in organs and to the intended and unintended consequences of such a practice. This article addresses these issues by exploring the tensions between ‘extrinsic’ and ‘intrinsic’ incentives, suggesting that donation might well decline were financial incentives introduced. It also contends that social relationship and social welfare policy would be transformed in negative ways and that a regulated market in organs would be extraordinarily difficult to achieve. Finally, it argues that organ sale would have a highly detrimental affect on medicine as a profession. The authors argue that establishing a market in organs may have an unintended adverse consequences on organ donation and a detrimental effect on the medical profession. See also editorial by Robert Gaston in this issue on page 1503.